Synthesis of enantiomerically enriched β-substituted analogs of (S)-α-alanine containing 1-phenyl-1H-1,2,3-triazole groups - Artavazd S. Poghosyan; Emma A. Khachatryan; Anna F. Mkrtchyan; Volodya Mirzoyan; Anahit M. Hovhannisyan; Karapet R. Ghazaryan; Ela V. Minasyan; Peter Langer; Ashot S. Saghyan (Amino Acids)
Abstract A synthesis of new enantiomerically enriched derivatives of (S)-α-aminopropionic acid, containing in the β-position 1,2,3-triazole groups coupled with a o-, m- and p-substituted phenyl residue, was developed based on Cu(I) catalyzed [3 + 2] cycloaddition of azides with alkynes. As the starting materials was used the square-planar Ni(II)complex of the Schiff base of propargylglycine with the chiral auxiliary BPB (Benzylprolylbenzophenone) and 1,4-substituted phenyl azides. The assignment of the (S)-absolute configuration of the α-carbon atom of the amino acid residue of the main diastereomeric complexes of the cycloaddition products was carried out on the basis of positive Cotton effects in the region of 480–580 nm of the circular dichroism spectra. The target amino acids were isolated from acid hydrolysates of diastereomeric complexes using ion-exchange demineralization and crystallization from aqueous ethanol. Additional confirmation of the absolute configuration and determination of the enantiomeric purity of the target amino acids were carried out by chiral HPLC analysis. As a result, seven new non-proteinogenic (S)-α-amino acids, containing in the β-position a 1,2,3-triazole moiety, were synthesized.